Pembekalan Karakter Bagi Guru TPQ-TPA Fosi Kecamatan Taman Kota Madiun - Wuryantoro Wuryantoro (JURNAL DAYA-MAS, 2021)
Abstractâ€” There are about 10 indicators of low social capital and character among the younger generation to worry about, namely increased teenage violence, poor use of language and words, strong peer group influence on violence, increased self-destructive behavior such as drugs, alcohol, free sex , the blurring of good and bad moral guidelines, the decline in work ethic, the lower respect for parents, the low individual responsibility for the country and the mutual suspicion of hatred among others. Academic pressure on the current education system is considered to be responsible for these problems, so that it requires the teacher to revitalize himself from a teacher who merely conveys the knowledge of being an educator who must be responsible for instilling morals. Lack of moral education, can make the brain stemÂ  and midbrain which is often called the reptile brain, more developed and dominant and makes someone will tend to behave violently. While the limbic and cortex parts of the brain that determine emotions, love and thinking become thin and weak. Conversely, if the limbic and cortex are dominant, reason and empathy will develop and become someone who is wise and wise. For all education and childcare are the main determining factors, which must be understood by educators (teachers, â€œustadzâ€)Â  and parents.Â Keywordsâ€”: Character;Â  educator; parents; social capital.